Biochemical and molecular basis of abiotic stress tolerance in barley - Kumar, Dinesh; Lal, Chuni; Bishnoi, Santosh Kumar; Verma, Ramesh Pal Singh; Singh, Gyanendra Pratap (Journal of Cereal Research, 2022)
Environment has very critical role for the plant growth and development and it is the deciding factor for the growing time and distribution of a crop plant in a particular geographical area. The abiotic stresses are bound to increase in the time to come, because of changing climatic conditions. To sustain the agricultural system, we need to get ready with the crop plants which have durable abiotic stress tolerance. Among the cultivable cereals, barley stands out in terms of abiotic stress tolerance and has the inherent capability to grow in harsh environments with limited resources. Attempt has been made in this article to compile the available information on some of the biochemical and molecular factors contributing to drought, salinity and heat tolerance of barley species. It is expected that this compilation may be useful for the crop improvement programmes in relation to abiotic stress tolerance.